The The Relationship Between Listening to Spotify Podcasts and Improving English Listening Skills Among EFL Students - Al Habsyi, Muhammad Najmi Al Habsyi; Abdul Syahid; Prananta Alvin Zikri; Helli Ramdanniah Liswati (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This study investigates the link between listening to Spotify podcasts and the enhancement of English listening skills among EFL (English as a Foreign Language) students. Employing a quantitative correlational design, the research examines how the frequency of podcast consumption influences students' listening comprehension abilities. A structured questionnaire was used to collect data on students' podcast listening behaviors, including frequency, duration, and preferred genres, as well as their perceived improvements in listening skills. The data were analyzed using Pearson’s correlation coefficient and regression analysis to evaluate the strength of the relationship. The study aims to provide insights into how podcasts, as an accessible and engaging resource, can support the development of English listening proficiency. The findings may offer valuable guidance for educators and learners in incorporating podcast listening into effective language learning strategies.